Effect of aged bone marrow microenvironment on mesenchymal stem cell migration - Yang, Yan-Mei (Age (Dordr), 2015)
Mesenchymal stem cells (MSCs) are known to have many notable features, especially their multiple differentiation ability and immunoregulatory capacity. MSCs are important stem cells in the bone marrow (BM), and their characteristics are affected by the BM microenvironment. However, effects of the BM microenvironment on the properties of MSCs are not well understood. In this study, we found that BM from aged mice decreased MSC colony formation. Flow cytometry data showed that the proportion of B220(+) cells in BM from aged mice was significantly lower than that in BM from young mice, while the proportion of CD11b(+), CD3(+), Gr-1(+), or F4/80(+) cells are on the contrary. CD11b(+), B220(+), and Ter119(+) cells from aged mice were not the subsets that decreased MSC colony formation. We further demonstrated that both BM from aged mice and young mice exhibited similar effects on the proliferation of murine MSC cell line C3H10T1/2. However, when cocultured with BM from aged mice, C3H10T1/2 showed slower migration ability. In addition, we found that phosphorylation of JNK (c-Jun N-terminal kinases) in C3H10T1/2 cocultured with BM from aged mice was lower than that in C3H10T1/2 cocultured with BM from young mice. Collectively, our data revealed that BM from aged mice could decrease the migration of MSCs from their niche through regulating the JNK pathway.